Temporal changes in the population structure of Dothistroma septosporum at the site of the first recorded outbreak in Poland. (11th October 2018) - Boroń, P.; Lenart‐Boroń, A.; Mullett, M.; Kraj, W.; Grad, B.; Kowalski, T.
Abstract : In this study, evolution of the genetic structure of the oldest known population of Dothistroma septosporum in Poland was analysed. Dothistroma needle blight was first recorded in Poland in 1990 in a 5‐year‐old plantation, meaning the population is relatively young in terms of evolution and genetic development. The preservation of DNA extracts from other studies allowed examination of the genetic variation of the pathogen over the span of a decade with the use of highly sensitive microsatellite markers. A number of evolutionary factors were identified that have shaped the genetic structure of this population over time. First, indications of the founder effect and the impact of selection were observed. Secondly, structure analysis provided evidence of the introduction of a new genetic component to the population structure after the pathogen had established. Finally, the impact of the reproductive mode on various components of the Domiarki population was examined, revealing the presence of genetic groups andstructure clusters with varying levels of sexual recombination. These results demonstrate how well established and genetically robust a new population of a pathogen may become in just a few decades, given favourable conditions, and how new introductions may facilitate this process.